Capacity and site readiness for hypertension control program implementation in Nigeria: A nationwide cross-sectional study - Innocent Ijezie Chukwuonye; Ejiroghene Martha Umuerri; Abigail Baldridge; Yekeen Ayodele Ayoola; Mahmoud Umar Sani; Okechukwu Samuel Ogah; Olanike Allison Orimolade; Miracle Erinma Chukwuonye; Kalu Ulu Kalu; Caleb Ogechi Raphael; Nyemike Simeon Awunor; Obatavwe Ukoba; et al. (PLoS ONE, 2026)
Background The aim of this study is to determine the capacity and readiness of Nigerian primary healthcare facilities to adopt a multi-level approach for the diagnosis, treatment, and control of hypertension. Methods Using a multi-stage sampling technique, 5 states were selected for the nationwide study, and 10 Primary Healthcare Centres (PHCs) were selected from each of the participating states. The 50 PHCs were evaluated using the World Health Organization-modified Service Availability and Readiness Assessment, focusing on the diagnosis and treatment of hypertension in Nigeria. The indicator scores for general and cardiovascular service preparedness were computed using the proportion of PHCs with accessible facilities, tools, diagnostic guidelines, and prescription drugs. Results A majority of PHCs (n = 43; 86%) reported having two or more full-time staff. The median number of full-time employees for the 50 PHCs was 6 (IQR = 2–9), and for the community health extension workers (CHEWs), the median was 2, the interquartile range (IQR) = 0–4. None of the PHCs had full-time physicians. Ninety-eight percent, 94%, and 84% of the 50 PHCs are able to provide screening services, diagnose, and confirm hypertension, respectively. In addition, 98% of the PHCs had functional blood pressure apparatus. However, only a minority of PHCs had the guidelines (24%), treatment algorithms (27%), and facilities. Most of the 50 PHCs (96%) use electronic patient records in their respective centres. Of the 50 PHCs studied, 66% had at least one 30-day antihypertensive treatment regimen in stock. The most commonly available drug classes were calcium channel blockers (72%), followed by diuretics (42%), central acting agents (38%), and angiotensin-converting enzyme inhibitors (36%). The median number of 30-day regimens in stock was 15 (IQR 0–132). Conclusion This first large-scale systematic assessment of capacity and readiness for a system-level hypertension control program within five states of Nigeria demonstrated implementation feasibility based on the workforce, equipment, and health information systems, but there is a critical need for health-worker training and provision of protocols for hypertension treatment and control, as well as some need to strengthen the essential medicine supply chain.